Successful treatment with rivaroxaban of cerebral venous thrombosis and bone marrow necrosis induced by pegaspargase: A case report and literature review. Issue 46 (November 2017) - Sui, Jingrui; Zhang, Yongming; Yang, Liqing; Wang, Hui; Xu, Junqing; Wei, Rongxia; Hao, Yaping; Wang, Xiaolei; Peng, Jun; Ma, Junjie
Abstract: Rationale: Pegaspargase has been used in the treatment of acute lymphoblastic leukemia with promising results. However, it has also been associated with several potentially serious complications, including thrombosis. Pegaspargase-induced cerebral venous thrombosis and bone marrow necrosis are very rare. Patient concerns: A 50-year-old female developed headache, weakness of the right lower extremity, fever, and bone pain after chemotherapy including pegaspargase for the treatment of acute lymphoblastic leukemia. Diagnoses: Her imaging studies and bone marrow examinations were compatible with cerebral venous thrombosis and bone marrow necrosis. Interventions: The patient received anticoagulation therapy with rivaroxaban. Outcomes: After treatment with rivaroxaban, she had a good outcome without major or minor bleeding. Lessons: Clinicians should be aware of the very rare but possible induction of bone marrow necrosis during pegaspargase treatment when there is necrosis in other organs. Because of its greater safety and convenience, rivaroxaban gains popularity over traditional anticoagulant drugs.